Dielectric behaviours of bio‐derived epoxy resins from cashew nutshell liquid. Issue 2 (15th December 2020) - Mu, Mulan; Vaughan, Alun
Abstract: In this study, four commercially available bio‐derived epoxy systems (extracted from cashew nutshell liquid) were prepared and characterised. The glass transition temperature ( T g ), dielectric spectroscopy, DC conductivity and breakdown properties of these epoxy resins were studied. Differential scanning calorimetry (DSC) demonstrated that the T g of the investigated systems ranged from 67 to 122°C. The DC conductivity was very low (<10 −16 S cm −1 ) and comparable to the conventional dielectrics at room temperature (RT). However, all systems showed a strong temperature dependence of the electrical conductivity and exhibited sharp increase around their respective T g . Arrhenius analysis led to activation energy, E a, values around 1 eV; higher E a values were observed in systems with a lower T g . Dielectric spectroscopy revealed a flat and low response at temperature below T g . However, both the real and imaginary permittivity increased with decreasing frequency at mid to low frequencies as the temperatures approached T g . The variations of AC breakdown strength of all samples were not statistically significant, but the DC breakdown strength of sample 2503A + 2002B was higher than the others, which might be due to reduced charge transport in this system. The results indicate that novel bio‐derived epoxy systems from renewable sources are potential alternatives for traditional petroleum‐based epoxy systems in certain insulation applications.